2006
DOI: 10.1634/stemcells.2006-0208
|View full text |Cite
|
Sign up to set email alerts
|

Human First-Trimester Fetal MSC Express Pluripotency Markers and Grow Faster and Have Longer Telomeres Than Adult MSC

Abstract: The biological properties of stem cells are key to the success of cell therapy, for which MSC are promising candidates. Although most therapeutic applications to date have used adult bone marrow MSC, increasing evidence suggests that MSC from neonatal and mid-gestational fetal tissues are more plastic and grow faster. Fetal stem cells have been isolated earlier in development, from first-trimester blood and hemopoietic organs, raising the question of whether they are biologically closer to embryonic stem cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
302
4
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 424 publications
(342 citation statements)
references
References 54 publications
25
302
4
9
Order By: Relevance
“…Evidence to support this assumption for enterocytes is sparse, but Guillot et al has recently shown that fetal mesenchymal stem cells express more pluripotency markers, have longer telomeres, and are more readily expandable and senesce later in culture than their adult counterparts. 28,29 . The present pilot study has additional limitations since the autotransplantation group is in other aspects not comparable to the allotransplantation group.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence to support this assumption for enterocytes is sparse, but Guillot et al has recently shown that fetal mesenchymal stem cells express more pluripotency markers, have longer telomeres, and are more readily expandable and senesce later in culture than their adult counterparts. 28,29 . The present pilot study has additional limitations since the autotransplantation group is in other aspects not comparable to the allotransplantation group.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were stained with primary antibodies (listed in Supplementary Table S1; Supplementary Data are available online at www.liebertpub.com/scd) then secondary antibody; donkey anti-mouse or anti-rabbit IgG ( Jackson ImmunoResearch Laboratories), before being mounted in VectaShield labeled with DAPI (Vector Labs) [24]. Fluorescence confocal laser scanning microscopy images were collected on a Leica TCS SP5 (X1000 PL APO oil objective).…”
Section: Fluorescence Immunostaining and Confocal Microscopymentioning
confidence: 99%
“…MSCs of the fetal liver have certain distinctive features, compared to such cells from other organs. Thus, they show higher proliferative activity than MSCs from the adult bone marrow [59,60], but their osteogenic and adipogenic potential is lower [61]. With respect to osteogenic capacity, they are also inferior to MSCs from other fetal organs [62,63].…”
Section: Mesenchymal Stromal Cells (Mscs)mentioning
confidence: 99%